Women's Participation in International Education: Gendered Barriers and Diplomatic Agency in South-South Student Mobility - Inun Fariha Nuhba; Harsuko Riniwati; Wike Wike (Bulletin of Community Engagement, 2026)
International student mobility has grown substantially over the past two decades, yet gender remains an undertheorized axis within this literature. This article examines the experiences of Indonesian female students who participated in IISMA, a government-sponsored international student exchange program, specifically in Malaysia. Focusing on their motivations, the gendered barriers they navigated, and the diplomatic roles they performed, this study draws on qualitative phenomenological interviews with eight female alumni and institutional data from two major Indonesian universities. The findings reveal that women represent 66 to 70 percent of awardees yet face persistent patriarchal constraints: parental gatekeeping over destination choices, gendered financial disadvantages, and administrative burdens compounded by marriage-readiness expectations. Guided by Raghuram and Sondhi's (2021) gendered mobilities framework and Collins and Bilge's (2020) intersectionality framework, we analyze how participants strategically negotiate overlapping structures of gender, class, and religious norms to achieve participation. Female participants further functioned as active agents of educational diplomacy by organizing cultural events, leading academic collaborations, and transferring knowledge beyond their formal student role. This study contributes to feminist scholarship on international student mobility by foregrounding women's voices and agency in a South-South context and highlights structural gaps that gender-neutral program designs fail to address.